Globalization and its role in nurturing artistic taste Conceptual art as a model (Journal of the College of Basic Education, 2022)
Globalization took a great place in the studies and its effects on economic, social and political manifestations became controversial at the end of the twentieth century, as globalization is the main feature at the present time, which has led to increasing interdependence among societies due to the increasing cultural and economic exchange, keeping abreast of development by developing his abilities and skills in thinking and logical analysis, and employing the sources of knowledge in the teaching and learning processes and helps in building an integrated personality capable of dealing with the data of art to develop cognitive awareness through the education of artistic taste in guiding the values ​​and principles to become a learner is an active element in society and education in general and raising the artistic taste and aesthetic perception in particular, as studies of globalization and artistic taste is necessary because it has acquired the attention of scholars, Means to find the possible means adopted by modern education and became the basis for all aesthetic education intact and includes the limits of research analysis of samples of paintings of contemporary art conceptual art , Communication to prepare the individual who is capable of also reviewed the first chapter a number of terms in the title of the research, the second chapter deals with the first: Globalization The concept and meaning Globalization is a present reality, through which it paves the ways and invented the means and communication and preparing the man who is capable of employing globalization. The second topic is the effect of globalization on the cultivation of artistic taste which is the practice of education to confront globalization and to interact with rapid changes in the development of thinking patterns and benefit from human knowledge, The theoretical framework was concluded by extracting the indicators from the previous studies and discussing them in order to benefit from the formulation of the items of the research tool (sample analysis form), The third chapter deals with the research procedures. In the current research, the analytical descriptive method was followed by the method of content analysis, in which the research society was selected, 15samples were selected and 3works of arts were selected. Eight fields of analysis were identified to reveal the role of globalization in the fourth chapter, the results included research, conclusions and recommendations.The results and conclusions reached by the researcher are as follows: - Globalization has contributed to the emergence of the art of advertising under the capitalist system in society, which is characterized by the capacity of production through the emergence of image culture that has dimensions within the trends of globalization Economic and social culture The impact of contemporary art on individualism and self-freedom in artistic production, whether related to the form or content or the use of new materials and techniques to achieve self-uniqueness, and to emphasize the personality of Alfred in the society of globalization and its transformations have had an impact on The behavior of the individual in particular and society in general, through its direct impact on the learner and then recommendations, proposals, sources, supplements and summary in English